Pediatric multiple sclerosis - Chabas, Dorothee; Strober, Jonathan; Waubant, Emmanuelle (Current neurology and neuroscience reports, 2008)
Diagnosing multiple sclerosis (MS) in a child is challenging because of the limited diagnostic criteria and their overlap with acute disseminated encephalomyelitis. Pediatric-onset MS patients are more likely to be male, have seizures, and have brainstem and cerebellar symptoms than adults, and are less likely to have spinal cord symptoms than adults. They mostly experience a relapsing-remitting course. Their initial brain MRI shows more frequent involvement of the posterior fossa, less well-defined ovoid lesions, and more confluent lesions that decrease over time in patients with prepubertal onset, making early diagnosis even more difficult. Although disability progression is slower than in adults, pediatric onset MS leads to significant disability at a younger age and may be worse in non-white patients (up to 50% in North America). The rareness of pediatric-onset MS has precluded enrollment in clinical trials. Thus, children are receiving off-label adult therapies without clear evidence of their effectiveness and limited knowledge of their tolerability.